FORMATION OF AXIOLOGICAL COMPETENCIES OF FUTURE ENGINEERS - O. A. Volkova (Высшее образование в России)
The article analyzes the possibilities of systematization of educational work on formation of axiological competences of future engineers in the context of the strategy of the University development as a center of educational-scientific, innovative, technological and social development of the region. The axiological competencies facilitate formation of a future engineer as a professional who has made a conscious choice. Ukhta State Technical University practices a unique model for psychological adaptation of students to organizational structure of potential employers. One of its main principles is creation of training situations which enable students to focus of their professionally important features and values and to stir up their professional reflexion.